2009
DOI: 10.1073/pnas.0909579106
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin receptor genetic variation relates to empathy and stress reactivity in humans

Abstract: Oxytocin, a peptide that functions as both a hormone and neurotransmitter, has broad influences on social and emotional processing throughout the body and the brain. In this study, we tested how a polymorphism (rs53576) of the oxytocin receptor relates to two key social processes related to oxytocin: empathy and stress reactivity. Compared with individuals homozygous for the G allele of rs53576 (GG), individuals with one or two copies of the A allele (AG/AA) exhibited lower behavioral and dispositional empathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
602
8
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 701 publications
(660 citation statements)
references
References 45 publications
(63 reference statements)
39
602
8
6
Order By: Relevance
“…This interaction was not significant (p = .20), indicating no ethnic differences in the stress-buffering role of OXTR rs53576; moreover, the magnitude of the OXTR GG × stress interaction was very similar between Caucasians (IRR = 0.91) and those of other ethnic groups (IRR = 0.87). While prior research on OXTR rs53576 has found no sex differences (e.g., Poulin et al, 2012;Rodrigues et al, 2009), female sex was a significant covariate in our analyses (see Table 1) and oxytocin is associated with many female-specific functions such as childbirth and lactation (Carter, 1998). Therefore, a second follow-up analysis examined whether the stress-buffering role of OXTR rs53576 differed between males and females.…”
Section: Oxtr and Stress Bufferingmentioning
confidence: 75%
See 4 more Smart Citations
“…This interaction was not significant (p = .20), indicating no ethnic differences in the stress-buffering role of OXTR rs53576; moreover, the magnitude of the OXTR GG × stress interaction was very similar between Caucasians (IRR = 0.91) and those of other ethnic groups (IRR = 0.87). While prior research on OXTR rs53576 has found no sex differences (e.g., Poulin et al, 2012;Rodrigues et al, 2009), female sex was a significant covariate in our analyses (see Table 1) and oxytocin is associated with many female-specific functions such as childbirth and lactation (Carter, 1998). Therefore, a second follow-up analysis examined whether the stress-buffering role of OXTR rs53576 differed between males and females.…”
Section: Oxtr and Stress Bufferingmentioning
confidence: 75%
“…Ideally, future work could examine proximal as well as distal indicators of oxytocin function and health, not all of which share this limitation, such as peripheral oxytocin assessment (e.g., Gouin et al, 2010). Finally, it was beyond the scope of the present research to examine the physiological mechanisms (e.g., modulated HPA axis and cardiovascular stress reactivity) by which charitable behavior and oxytocin might buffer the impact of stressful events (Chen et al, 2011;Norman et al, 2012;Rodrigues et al, 2009). Future research should examine whether the OXTR rs53576 SNP and prosocial behavior interact in a compensatory manner to buffer physiologic markers of stress, and if so, whether these effects can predict health outcomes.…”
Section: Contributions Limitations and Future Directionsmentioning
confidence: 98%
See 3 more Smart Citations